2023
DOI: 10.7324/japs.2023.133107
|View full text |Cite
|
Sign up to set email alerts
|

The in-silico potential of Andrographis paniculata phytocompounds as antiviral for the treatment of COVID-19: A systematic review

Abstract: Since the outbreak of coronavirus disease 2019 (COVID-19), many studies have been conducted to develop definitive therapeutic agents for this viral disease. The in-silico method has become the best solution for the initial step in discovering potential antiviral compounds. Several phytocompounds from a medicinal plant, Andrographis paniculata, were reported to have activity inhibiting SARS-CoV-2 proteins. The present systematic review aims to determine the potency of A. paniculata compounds against COVID-19. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Eurycoma harmandiana, Sophora avescens and Andrographis paniculata contain phyto-compounds, such as terpenoids, avonoids and their glycosides, act against SARS-COV-2 PLpro and Mpro proteases. 80,173,182 A combined approach for in silico screening towards repositioning of FDA-approved drug candidates for anticoronaviral therapy has identied Ouabain, which is an antiarrhythmic drug of plant origin, as a dual inhibitor for both PLpro and Mpro enzymes. 183 Using in vitro studies and in silico screening, it has been shown that some purine nucleosides inhibiting nucleoside phosphorylase enzymes, such as Forodesine and Riboprine, revealed strong repurposing potential against two broadly conserved SARS-CoV-2 enzymes, such as RNA-dependent RNA polymerase (RdRp) and 3 ′ -to-5 ′ exoribonuclease (ExoN), irrespective of the SARS-CoV-2 variant type (Fig.…”
Section: Dual and Multi-targeting Inhibitors Of Sars-cov-2 Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…Eurycoma harmandiana, Sophora avescens and Andrographis paniculata contain phyto-compounds, such as terpenoids, avonoids and their glycosides, act against SARS-COV-2 PLpro and Mpro proteases. 80,173,182 A combined approach for in silico screening towards repositioning of FDA-approved drug candidates for anticoronaviral therapy has identied Ouabain, which is an antiarrhythmic drug of plant origin, as a dual inhibitor for both PLpro and Mpro enzymes. 183 Using in vitro studies and in silico screening, it has been shown that some purine nucleosides inhibiting nucleoside phosphorylase enzymes, such as Forodesine and Riboprine, revealed strong repurposing potential against two broadly conserved SARS-CoV-2 enzymes, such as RNA-dependent RNA polymerase (RdRp) and 3 ′ -to-5 ′ exoribonuclease (ExoN), irrespective of the SARS-CoV-2 variant type (Fig.…”
Section: Dual and Multi-targeting Inhibitors Of Sars-cov-2 Enzymesmentioning
confidence: 99%
“…Eurycoma harmandiana , Sophora flavescens and Andrographis paniculata contain phyto-compounds, such as terpenoids, flavonoids and their glycosides, act against SARS-COV-2 PLpro and Mpro proteases. 80,173,182…”
Section: Promising Targets For Pharmacological Action On Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation